Tissue bioanalysis of biotherapeutics and drug targets to support PK/PD. (November 2012) - Neubert, Hendrik; Fountain, Scott; King, Lindsay; Clark, Tracey; Weng, Yan; O'Hara, Denise M; Li, Wenlin; Leung, Sheldon; Ray, Chad; Palandra, Joe; Ocaña, Mireia Fernández; Chen, Jianqing; et al.
Contemporary drug discovery leverages quantitative modeling and simulation with increasing emphasis, both to gain deeper knowledge of drug targets and mechanisms as well as improve predictions between preclinical models and clinical applications, such as first-in-human dose projections. Proliferation of novel biotherapeutic modalities increases the need for applied PK/PD modeling as a quantitative tool to advance new therapies. Of particular relevance is the understanding of exposure, target binding and associated pharmacology at the target site of interest. Bioanalytical methods are key to informing PK/PD models and require assessment of both PK and PD end points. Where targets are sequestered in tissues (noncirculating), the ability to quantitatively measure drug or biomarker in tissue compartments becomes particularly important. This perspective provides an overview of contemporary applications of quantitative bioanalysis in tissue compartments as applied to PK and PD assessments associated with novel biotherapeutics. Case studies and key references are provided.